IMPLEMENTING DATA-DRIVEN LEARNING INTO ENGLISH GRAMMAR PEDAGOGY: A BASIC INTERPRETATIVE STUDY IN A VOCATIONAL CLASSROOM IN KARAWANG - Abdul Muis Muhyidin (Jurnal Guru Dikmen dan Diksus, 2019)
This study described an implementation of data driven learning in teaching English grammar. To answer of research questions, this study used a qualitative approach with basic interpretative study. The study was conducted in one of vocational high schools in Karawang, involving one English teacher and six students as research subject. To investigate to what extent English teacher applied data-driven learning in teaching English grammar, this study collected data from classroom observation, interviews and studying documents. The results showed that the data driven learning was implemented in teaching grammar through four stages of teaching procedures, including pattern formation through exploring BNC data, explicit explanation from teacher to conform or to correct students’ findings, follow-up exercises through homework, then classroom production and teacher’s feedback on it.